Linguistics from the Perspective of the Theory of Models in Empirical Sciences: From Formal to Corpus Linguistics - Grabinska, Teresa and Zielinska, Dorota (Journal of Technical Writing and Communication, 2010)
The authors examine language from the perspective of models of empirical sciences, which discipline studies the relationship between reality, models, and formalisms. Such a perspective allows one to notice that linguistics approached within the classical framework share a number of problems with other experimental sciences studied initially exclusively within that framework because of making the same sort of assumptions. By examining solutions to some of these problems found in contemporary science, the authors point out alternative approaches, which could be relevant for linguistics research, and some of which have already been tested in language studies. In particular, Corpus Linguistics is presented as an especially promising approach, positioned to avoid many of the pitfalls of the classical framework. Consequently, it seems that the future of linguistics, from theoretical to applied, such as Technical Writing, must be embraced by Corpus Linguistics research.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMjE5MC90dy40MC40LmI